2021
DOI: 10.1098/rsbl.2021.0356
|View full text |Cite
|
Sign up to set email alerts
|

Human voice pitch measures are robust across a variety of speech recordings: methodological and theoretical implications

Abstract: Fundamental frequency ( f o ), perceived as voice pitch, is the most sexually dimorphic, perceptually salient and intensively studied voice parameter in human nonverbal communication. Thousands of studies have linked human f o to biological and social speaker traits and life outcomes, from reproductive to economic. Critically, researchers have used myriad speech stimuli to measure f o and infer its funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…We recorded six native Turkish speakers -three females with an average age of 38 and three males with an average age of 40 -making the following policy statements in Turkish: 'Please vote for me' and 'I will annually allocate X TL per person'. Pisanski et al [2021] shows that studies on voice pitch obtain comparable results over different types of recordings, such as a series of vowels, a single word, or a sentence as in our case. We recorded multiple speakers to reduce any individual-level effect of other vocal characteristics such as tone of the voice, rhythm, or tempo.…”
Section: Experimental Stimulisupporting
confidence: 67%
“…We recorded six native Turkish speakers -three females with an average age of 38 and three males with an average age of 40 -making the following policy statements in Turkish: 'Please vote for me' and 'I will annually allocate X TL per person'. Pisanski et al [2021] shows that studies on voice pitch obtain comparable results over different types of recordings, such as a series of vowels, a single word, or a sentence as in our case. We recorded multiple speakers to reduce any individual-level effect of other vocal characteristics such as tone of the voice, rhythm, or tempo.…”
Section: Experimental Stimulisupporting
confidence: 67%
“…A recent study has shown that individual differences in voice fundamental frequency (f o , perceived as voice pitch) are preserved across speech types (Pisanski, Groyecka-bernard, et al, 2021). Pisanski and colleagues (2021) analyzed f o in six different types of neutral speech utterances (from vowels to longer bouts of spontaneous speech) and showed that interindividual differences in this salient voice property are highly robust, such that a person's voice pitch when speaking a vowel sound correlates strongly with their voice pitch when speaking a full paragraph of free speech.…”
Section: Introductionmentioning
confidence: 99%
“…Several basic vowel sounds are also shared across most languages (see the International Phonetic Alphabet) making them cross-culturally comparable. Moreover, as shown in a recent study by Pisanski and colleagues 12 , a person’s mean f o (roughly perceived as their modal voice pitch) can also be reliably measured from simple vowel sounds. Thus, although they are very short in duration and largely lack prosodic contrasts, vowels constitute a standardised and comparable vocal stimulus, similar across languages and free of the potential confounds of verbal content.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, if listeners’ voice-based judgments are not substantially affected by the type of speech produced by the vocaliser, this would suggest that studies using different kinds of speech may be comparable, and that any differences in their results are not likely due to the type of speech stimuli used. It would also offer further support that information encoded in the nonverbal vocal parameters of the human voice, such as in voice pitch, is relatively stable and largely impervious to changes in modal speech complexity 12 , 13 .…”
Section: Introductionmentioning
confidence: 94%